2011
DOI: 10.5402/2011/735936
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Health Status of Persons Seeking Treatment for Exposure to Libby Amphibole Asbestos

Abstract: A cross-sectional exploratory study was conducted to describe the psychosocial health status of persons seeking health care for exposure to Libby amphibole asbestos (LAA). Health indicators including depression, stress, acceptance of illness, and satisfaction with access and financial aspects of care were obtained via electronic and paper-pencil survey. The exposure pathway and demographic data were gleaned from the health record. Of the 386 participants, more than one-third (34.5%) demonstrated significant le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…In other studies (N=386), more than 34% of participants exposed to Libby amphibole asbestos exhibited psychological distress (Weinert, et al, 2011), were less satisfied with access and financial aspects of care (Winters, et al, 2011) than persons with other chronic illnesses, and demonstrated poorer health-related quality of life when compared with the general population. In a study (Cook & Hoas, 2007) to examine the ethical implications residents faced when dealing with uncertainty and distress that accompany environmental contamination, researchers found that recovery in Libby was far from complete, noting that communication between researchers and community members was critical and further research was needed to better understand the long term health effects and impact of the man-made disaster on persons and communities exposed to Libby amphibole asbestos.…”
Section: Resultsmentioning
confidence: 91%
“…In other studies (N=386), more than 34% of participants exposed to Libby amphibole asbestos exhibited psychological distress (Weinert, et al, 2011), were less satisfied with access and financial aspects of care (Winters, et al, 2011) than persons with other chronic illnesses, and demonstrated poorer health-related quality of life when compared with the general population. In a study (Cook & Hoas, 2007) to examine the ethical implications residents faced when dealing with uncertainty and distress that accompany environmental contamination, researchers found that recovery in Libby was far from complete, noting that communication between researchers and community members was critical and further research was needed to better understand the long term health effects and impact of the man-made disaster on persons and communities exposed to Libby amphibole asbestos.…”
Section: Resultsmentioning
confidence: 91%
“…Amerika'da asbeste maruz kalmış ve yardım almak için kliniğe başvurmuş kişilerin psikososyal sağlık durumlarını araştıran bir çalışmada bireylerin %34,5'inde psikososyal bozukluk olduğu ortaya konmuştur 13 . Barak ve arkadaşlarının asbeste maruz kalan elektrik atölyesinde çalışan işçilerde yapmış oldukları bir çalışmada, işçilerin %50'sinde Post Travmatik Stres Bozukluğu ortaya çıktığı belirtilmiştir 14 .…”
Section: Discussionunclassified
“…Weinert ve arkadaşlarının yapmış olduğu çalışmada da yaş ve cinsiyetin depresyon ve stres düzeylerini etkilediği belirlenmiştir. Genç yaşta olanların ve kadınların depresyon ve stres düzeylerinin daha yüksek olduğu hesaplanmıştır 13 . Hermanns ve arkadaşları, kadın olmanın anksiyete ve depresyon için risk etkeni olduğunu bildirmişlerdir 21 .…”
Section: Discussionunclassified
“…Furthermore, the finding of pleural and interstitial abnormalities and diminished pulmonary function in persons with low lifetime cumulative amphibole fibre exposure, for example, non-vermiculite worker or household member of a vermiculite worker, is important given the widespread distribution and use of vermiculite ore in private and commercial applications. Holistic healthcare that addresses the psychosocial and physiological aspects of health is an important consideration in persons exposed to or living with the health effects of LAA 28. Routine screening of individuals at risk for ARD and those with pleural or interstitial abnormalities using tools like the SGRQ is essential to the provision of early psychosocial intervention and support for respiratory-related QOL issues.…”
Section: Discussionmentioning
confidence: 99%
“…The association between specific exposure pathways and radiographic abnormalities has been reported19 20 24–26 Scant information has been published on overall responses to exposure, for example, access to healthcare27 and psychosocial ramifications28 in this population. The quality of life of persons exposed to Libby amphibole asbestos (LAA) has not been described.…”
Section: Introductionmentioning
confidence: 99%